MENGENALKAN PERAN SERTA MASYARAKAT DALAM PENEGAKAN NEGARA HUKUM DAN HAK ASASI MANUSIA DI BANJARSARI, SURAKARTA - Huda, Salahudin Khairul; Najah, Umi; Shalihah, Aisyah Mar'atus; Mustofa, Abid Abiyyu Nur (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Indonesia is a constitutional state as stated in the 1945 Constitution. For Indonesia, the enforcement of human rights is a principle that is upheld. As a nation that has experienced colonialism, the founder of our Republic is aware of the meaning of human rights in state activities. The purpose of conducting this research is to introduce information related to the rule of law and human rights, to open public knowledge about human rights and to make people aware that the role of the community is very much needed in protecting the human rights of Indonesian citizens and the need to increase the sense of nationalism of local residents. The activity is centered on the introduction of human rights to the public through media exposure about the rule of law and human rights. The implementation method for this community service is by interviewing, media exposure, discussion, activity reports to the person in charge of the community. The active role of community members in maintaining and reducing pollution and moral damage in respecting the human rights of fellow citizens that occurs in Indonesia, especially in Banjarsari District, Surakarta.